OPTIMALISASI OTONOMI KHUSUS PAPUA DALAM PENINGKATAN KESADARAN HUKUM MASYARAKAT GUNA MEREDAM KONFLIK DAN KEKERASAN - nur rohim (Universitas Lampung, 2014)
Special autonomy has been given to the people of Papua was not automatically change the demand to break away from the Unitary Republic of Indonesia. Even conflict and violence are still common, not much the case in the period before the special autonomy granted. Legal awareness that should have been animating soul Indonesian citizens, to the condition of Papua away than they should. Disputes, inter-tribal warfare, even against migrants have often heard. The tribes in Papua does have a unique custom that sees itself as the center of the universe, the best of all. Papua leadership so very, very difficult to put together. Even if the idea is basically the idea Papuanisation fruit Dutch education is taught to the people of Papua to foster its own distinct sense of nationalism with the nation of Indonesia. The result appears separatist movements such as the Free Papua Organization (OPM) and the West Papua National Committee (KNPB). To avoid the disintegration of the nation, the central government issued Law No. 21 of 2001 on Special Autonomy for Papua. That is, the people of Papua entitled to set its own country with the regulations stipulated by law. This legislation is expected to become a sedative from the turmoil in Papua. Although it remains to be an evaluation and improvements here and there. Such as optimizing the alignment of the central government towards the implementation of special autonomy, optimizing the role of the Papuan People's Assembly, and optimization of special autonomy fund supervision. So that the common goal of creating prosperity, welfare and peace of Indonesian citizens in Papua indigenous ancestral lands can be realized. Keywords: Special Autonomy, Law Awareness, Conflict and Violence